The ambivalent myth of Tuva in the twentieth century - Shafranskaya, Eleonora F; Garipova, Gulchira T.; Shaimerdenova, Nursulu Zh. (The New Research of Tuva, 2024)
The article analyzes the process of mythologization of Tuva in the twentieth century. It led to the birth of an ambivalent myth about Tuva as, on the one hand, a wild, “uncivilized” land, on the other hand, as a hidden spiritual center of the world. The relevance of the article relates to the study of the permanent reproductive function of the myth, as well as with the insufficiently studied mythologization of the Tuvan locus. The attraction to Tuva as a mysterious country gives rise to two vectors of mythologization: 1) critical texts and 2) texts immersing in a foreign culture. The object of this study is the texts of the second type. Travelers attracted to Tuva by several attractive factors, including postage stamps from the period of the Tuvan People’s Republic, throat singing, the topographic center of Asia, give rise to an ambivalent myth about Tuva. At first, Tuva is always a mystery, an unknown land, terra incognita, and later — in the process of mythologization by strangers / others: the land is wild, “uncivilized” and some hidden spiritual center. The story of R. Feynman and R. Leighton, who planned a trip to Tuva, served as material for analysis. It formed the basis for R. Layton’s novel “Tuva or bust!” in 1991 and the film about Richard Feynman in 1988. The travelogue by O. Menchen-Helfen “Journey to Asian Tuva” in 1931 and the documentary film by R. Belich “Genghis Blues” in 1999 are also considered.